Plasmatic Concentrations of ADMA and Homocystein in Llama (Lama glama) and Regulation of Arginase Type II: An Animal Resistent to the Development of Pulmonary Hypertension Induced by Hypoxia - López, Vasthi; Moraga, Fernando A.; Llanos, Anibal J.; Ebensperger, German; Taborda, María I.; Uribe, Elena (Frontiers in Physiology, 2018)
There are animal species that have adapted to life at high altitude and hypobaric hypoxia conditions in the Andean highlands. One such species is the llama (Lama glama), which seem to have developed efficient protective mechanisms to avoid maladaptation resulting from chronic hypoxia, such as a resistance to the development of hypoxia -induced pulmonary hypertension. On the other hand, it is widely known that different models of hypertension can arise as a result of changes in endothelial function. The respect, one of the common causes of deregulation in endothelial vasodilator function have been associated with down-regulation of the NO synthesis and an increase in plasma levels of asymmetric dimethylarginine (ADMA) and homocysteine. Additionally, it is also known that NO production can be regulated by plasma levels of L-arginine as a result of the competition between nitric oxide synthase (NOS) and arginase. The objective of this study, was to determine the baseline concentrations of ADMA and homocysteine in llama, and to evaluate their effect on the arginase pathway and their involvement in the resistance to the development of altitude-induced pulmonary hypertension. METHOD: Lowland and highland newborn sheep and llama were investigated near sea level and at high altitude. Blood determinations of arterial blood gases, ADMA and homocysteíne are made and the effect of these on the arginase activity was evaluated. RESULTS: The basal concentrations of ADMA and homocysteine were determined in llama, and they were found to be significantly lower than those found in other species and in addition, the exposure to hypoxia is unable to increase its concentration. On the other hand, it was observed that the llama exhibited 10 times less arginase II activity as compared to sheep, and the expression was not induced by hypoxia. Finally, ADMA y Hcy, has no effect on the type II arginase pathway. CONCLUSION: Based on our results, we propose that low concentrations of ADMA and homocysteine found in llamas, the low expression of arginase type II, DDAH-2 and CBS, as well as its insensitivity to activation by homocysteine could constitute an adaptation mechanism of these animals to the hypoxia.